1996
DOI: 10.1007/bf00041395
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and analysis of the gene for cystathionine ?-synthase from Arabidopsis thaliana

Abstract: A cDNA clone, CGS1, encoding cystathionine gamma-synthase (CGS) from Arabidopsis thaliana was selected by complementation of CGS mutant strain of Escherichia coli (metB). Cells expressing CGS1 can grow on medium lacking Met and contain CGS enzyme activity. Genomic DNA blot analysis of A. thaliana revealed that there is a single gene homologous with CGS1. A genomic fragment carrying CGS1 was cloned and sequenced. Through combined analysis of the cDNA and genomic clone it was determined that the CGS1 coding sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 35 publications
2
33
0
Order By: Relevance
“…2), showing that both possess CGS activity, confirming that the N-terminal domain of the mature plant CGS is not essential for its catalytic activity. These results extend the data of a previous report showing that deletion of part of the plantspecific N-terminal region of the mature Arabidopsis CGS enables complementation of an E. coli metB mutant (Kim and Leustek, 1996).…”
Section: Plant Cgss Contained An Extended N-terminal Region In Comparsupporting
confidence: 89%
“…2), showing that both possess CGS activity, confirming that the N-terminal domain of the mature plant CGS is not essential for its catalytic activity. These results extend the data of a previous report showing that deletion of part of the plantspecific N-terminal region of the mature Arabidopsis CGS enables complementation of an E. coli metB mutant (Kim and Leustek, 1996).…”
Section: Plant Cgss Contained An Extended N-terminal Region In Comparsupporting
confidence: 89%
“…Molecular cloning, comparison to bacterial enzymes, and in vitro assays of enzyme activity have confirmed that the A. thaliana At3g01120 gene encodes cystathionine γ-synthase (EC 2.5.1.48; Figure 7), the committing enzyme for methionine biosynthesis (Kim and Leustek, 1996;Ravanel et al, 1998). Another A. thaliana locus, At1g33320, has 76% amino acid sequence identity to At3g01120, but there is as yet no confirmation that this gene encodes a cystathionine γ-synthase.…”
Section: Methionine Biosynthesismentioning
confidence: 99%
“…Since alliinase is supposed to be a vacuolar protein [3], it needs a signal peptide [15]; ASA, A. sativum alliinase [15]; ATCBL, Arabidopsis thaliana cystathionine β-lyase [41]; CGS-1, A. thaliana cystathionine γ-synthase [42]; CYS-3, S. cerevisiae cystathionine γ-lyase [43]; MET17, S. cerevisiae cystathionine γ-synthase [45]; METC, S. cerevisiae cystathionine β-lyase [46]; METZ, Pseudomonas aeruginosa O-succinyl homoserine sulfhydrylase [47]; MGL, P. putida methionine γ-lyase [48].…”
Section: Molecular Comparison With Alliinases From Other Plantsmentioning
confidence: 99%